TI_GERICHTE 16.2019.6 vom 21. März 2019 , Espulsione dall'ente locato - tutela giurisdizionale nei casi manifesti - TI Tribunale d'appello (2019)
Espulsione dall'ente locato - tutela giurisdizionale nei casi manifesti